Generations, Education and Common Values: a study on five Italian cohort-generations, from the Reconstruction to Gen Z - Bonanni, Matteo (SocietàMutamentoPolitica, 2025)
The concept of values has long been at the core of sociological discussions. Considering the extensive range of literature and diverse approaches, there is a clear gap to be addressed. Lyons and colleagues (2005, 2007) have noted the absence of studies investigating value differences between generations. In this paper, data were used from the Italian subsamples of the European Social Survey (ESS) for the years 2018, 2020, 2022 to provide evidence to fill part of this gap. The paper’s goals are to fill the gap in literature and determine if values can differentiate generations that are close in time. These goals will be pursued using the Basic Human Values theory of S. H. Schwartz that are currently part of the ESS questionnaire and the cohort-generation tool for the comparison. Five different cohort-generations were considered: the Reconstruction generation (born between 1927 and 1948), the Baby Boom generation (born between 1948/49 and 1968), Generation X (born between 1968/69 and 1979), Y (1979/80 and 1995) and Z (1995/96 and 2008). The last, complementary goal is to understand whether education (which can be considered the biggest change that has affected generations over time) can describe the changes in values over generations. This will be done in line with an awareness of the fundamental role of education and its potential to change values, attitudes and expectations.